Evaluasi Penerapan Sistem Pengendalian Internal dan Siklus Penjualan Online Berbasis WhatsApp pada CV Kurnia - Raudlatishafa, Ershazkiya; Widajantie, Tituk Diah (VISA: Journal of Vision and Ideas, 2024)
In the era of globalization that continues to grow and develop, many companies are competing to expand their market reach and increase their income, one of which is by selling online. Online sales have revolutionized the way we do business, opening the gates of limitless opportunities in the digital era. This research aims to evaluate the implementation of the online sales cycle internal control system at CV Kurnia, explore the CV Kurnia online sales system. This research uses qualitative research methods which will be explained in a descriptive manner. The type of data that researchers use in this research is qualitative data, namely from the results of interviews and personal documentation. The evaluation results of CV Kurnia's internal control system show that the Company has implemented internal control which can be said to be quite good. However, there are still some shortcomings. Of the five elements of COSO internal control that still need to be improved are information and communication. Because there is still some limited information regarding online sales. The results of online sales cycle research have shown that online sales are running well and regularly.